2018
DOI: 10.3892/or.2018.6914
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed PLAGL2 transcriptionally activates Wnt6 and promotes cancer development in colorectal cancer

Abstract: Researchers hold the view that PLAGL2 is overexpressed in many malignancies and that it can promote tumor proliferation, migration, invasion and self-renewal; however, there is no evidence revealing a relationship between PLAGL2 and colorectal cancer (CRC). In the present study, genes that are overexpressed in CRC were screened using the COSMIC database and GEPIA database and the expression of PLAGL2 in carcinoma tissues and pericarcinomatous tissues was detected by RT-qPCR and western blot assays. A Cell Coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 34 publications
4
53
1
Order By: Relevance
“…According to mechanism investigation, we confirmed that miR-1270 could interact with PLAGL2. PLAGL2 has been confirmed as an oncogene in colorectal cancer [47] and bladder urothelial The potential mRNAs that could bind with miR-1270 were searched from PITA, RNA22, miRmap and microT databases. c qRT-PCR examined the expressions of predicted mRNAs (PLAGL2, TCF12 and GLI3) in LUAD cell lines and normal human lung epithelial cell line.…”
Section: Discussionmentioning
confidence: 99%
“…According to mechanism investigation, we confirmed that miR-1270 could interact with PLAGL2. PLAGL2 has been confirmed as an oncogene in colorectal cancer [47] and bladder urothelial The potential mRNAs that could bind with miR-1270 were searched from PITA, RNA22, miRmap and microT databases. c qRT-PCR examined the expressions of predicted mRNAs (PLAGL2, TCF12 and GLI3) in LUAD cell lines and normal human lung epithelial cell line.…”
Section: Discussionmentioning
confidence: 99%
“…It is apparently upregulated during intestinal development and regeneration as well as in CRC cells (51,52). Overexpression or activation of Wnt6 could promote CRC development via activating the canonical Wnt signaling (53,54). Moreover, a significant upregulation of methylation in Wnt6 gene was also detected in CRC samples (109), and the Wnt6 rs6747776 polymorphism may participate in the increased risk of CRC associated with excessive saturated fat intake (110).…”
Section: Wnt16mentioning
confidence: 99%
“…Although DNA methylation was clearly associated with WNT6 expression in glioma, this association was not universal. After ruling out the potential regulation of WNT6 by CAV1, UCA1 , and PLAGL2 in GBM (contrasting to what was previously described in gastric, bladder, and colorectal cancers (Fan et al , ; Li et al , ; Yuan et al , )), we showed that HOXA9, an oncogenic transcription factor whose expression has been associated with increased GBM aggressiveness (impacting on several hallmarks of cancer, increasing cell viability, migration, resistance to TMZ, and tumor growth in a subcutaneous mouse model, while decreasing mice OS in an orthotopic mouse model) and patients’ poor survival (Costa et al , ; Pojo et al , ), is one of the WNT6 transcriptional regulators in GBM (Fig. ), binding to its promoter region.…”
Section: Discussionmentioning
confidence: 99%